Modeling of Dynamic Systems - De Silva, Clarence W. (London : Taylor and Francis, 2017)
"MODELING OF DYNAMIC SYSTEMS takes a unique, up-to-date approach to systems dynamics and related controls coverage for undergraduate students and practicing engineers. It focuses on the model development of engineering problems rather than response analysis and simulation once a model is available, though these are also covered. Linear graphing and bond graph approaches are both discussed, and computational tools are integrated thoughout. Electrical, mechanical, fluid, and thermal domains are covered, as are problems of multiple domains (mixed systems); the unified and integrated approaches taken are rapidly becoming the standard in the modeling of mechatronic engineering systems."--Provided by publisher.
Chapter 1 Introduction to Modeling / Clarence W. de Silva -- chapter 2 Basic Model Elements / Clarence W. de Silva -- chapter 3 Analytical Modeling / Clarence W. de Silva -- chapter 4 Model Linearization / Clarence W. de Silva -- chapter 5 Linear Graphs / Clarence W. de Silva -- chapter 6 Frequency-Domain Models / Clarence W. de Silva -- chapter 7 Transfer-Function Linear Graphs / Clarence W. de Silva -- chapter 8 Simulation Block Diagrams / Clarence W. de Silva -- chapter 9 Response Analysis and Simulation / Clarence W. de Silva.
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY & ENGINEERING -- Electrical; Simulation methods; System analysis